Providers’ Perspectives on Provision of Family Planning to HIV-Positive Individuals in HIV Care in Nyanza Province, Kenya - Sara J. Newmann; Kavita Mishra; Maricianah Onono; Elizabeth A. Bukusi; Craig R. Cohen; Olivia Gage; Rose Odeny; Katie D. Schwartz; Daniel Grossman (AIDS Research and Treatment)
Objective. To inform an intervention integrating family planning into HIV care, family planning (FP) knowledge, attitudes and practices, and perspectives on integrating FP into HIV care were assessed among healthcare providers in Nyanza Province, Kenya. Methods. Thirty-one mixed-method, structured interviews were conducted among a purposive sample of healthcare workers (HCWs) from 13 government HIV care facilities in Nyanza Province. Structured questions and case scenarios assessed contraceptive knowledge, training, and FP provision experience. Open-ended questions explored perspectives on integration. Data were analyzed descriptively and qualitatively. Results. Of the 31 HCWs interviewed, 45% reported previous FP training. Few providers thought long-acting methods were safe for HIV-positive women (19% viewed depot medroxyprogesterone acetate as safe and 36% viewed implants and intrauterine contraceptives as safe); fewer felt comfortable recommending them to HIV-positive women. Overall, providers supported HIV and family planning integration, yet several potential barriers were identified including misunderstandings about contraceptive safety, gendered power differentials relating to fertility decisions, staff shortages, lack of FP training, and contraceptive shortages. Conclusions. These findings suggest the importance of considering issues such as patient flow, provider burden, commodity supply, gender and cultural issues affecting FP use, and provider training in FP/HIV when designing integrated FP/HIV services in high HIV prevalence areas.